2016
DOI: 10.1002/app.43535
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, electrical and antibacterial properties of sericin/poly(vinyl alcohol)/poly(vinyl pyrrolidone) composites

Abstract: In this study, we focused on the fabrication of poly(vinyl alcohol) (PVA)/poly(vinyl pyrrolidone) (PVP)/sericin composites via a simple solution-blending method. The composites were characterized by Fourier transform infrared (FTIR) spectroscopy, UV spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetry, thermogravimetric analysis (TGA), and measurements of the conductivity, tensile strength, and antibacterial activity against Staphylococcus aureus. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…It was observed that the incorporation of silk fiber increased the intensity as well as the crystallinity of the film composite. The higher crystallinity value of the composite film could be attributed to the nucleating effect caused due to the addition of the silk fibers trapped in the macromolecular chains of the blends as a result of the polar interaction of the functional groups of silk with the matrix .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the incorporation of silk fiber increased the intensity as well as the crystallinity of the film composite. The higher crystallinity value of the composite film could be attributed to the nucleating effect caused due to the addition of the silk fibers trapped in the macromolecular chains of the blends as a result of the polar interaction of the functional groups of silk with the matrix .…”
Section: Resultsmentioning
confidence: 99%
“…From the TGA, it can be seen that the PVA/PVP film as well as the film composites show three decomposition steps. For the pure blend, the initial decomposition occurred at 70°C–140°C with a mass loss of 7.4% due to the loss of bound water molecules and acetic acid in the polymer . Maximum degradation occurred between 200°C and 365°C accompanied by a major weight loss of about 42% due to the melting and breakdown of the blend segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular calcium-based nanoparticles have shown to have therapeutic benefits when used in cutaneous wound repair (Kawai et al, 2011). On the other hand, sericin has high antioxidant potential (Prasong, 2011;Kumar and Mandal, 2017), antibacterial activity (Ramesan et al, 2016), mitogenic effect on cells (Terada et al, 2005), potential to inhibit inflammation (Aramwit et al, 2012a), and ability to retain hydration (Padamwar et al, 2005). In the study of Aramwit et al, a sericin-based therapeutic cream formulation improved healing by promoting collagen production and rapid re-epithelialization in rat skin wounds (Aramwit et al, 2009(Aramwit et al, , 2013.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Polymer blend nanocomposites have attracted extensive interest on the fabrication of advanced engineering materials with good mechanical, electrical and optical properties. Such materials can be achieved through employing proper functional groups containing polymers . The mechanical, thermal and electrical properties of biopolymer blends can further be improved mixing metal nanoparticles with the blend matrix.…”
Section: Introductionmentioning
confidence: 99%